Conception vessel acupuncture research regularity in the treatment of diminished ovarian reserve: a multi-center, large-sample prospective cohort study protocol - Zhang, Xiaoyu; Sun, Hao; Zhang, Na; Mou, Zijun; Xia, Qingchang; Du, Dongqing; Ma, Yuxia (Frontiers in Endocrinology, 2024)
Background: Diminished ovarian reserve (DOR) refers to a decrease in the number or quality of oocytes in the ovarian cortex, which is a degenerative disease of the reproductive system, and can further develop into premature ovarian failure. There are few studies on acupuncture and moxibustion for DOR, which are still in the exploratory stage. Methods/design: This study was a real-world case registry study. According to whether the subjects received conception vessel acupuncture or not, they were divided into the basic treatment combined with conception vessel acupuncture group and the basic treatment group. A total of 1221 patients with DOR were enrolled and treated for 12 weeks. The percentage of patients with ≥30% improvement in anti-Müllerian hormone (AMH) was evaluated at the end of week 12. Secondary outcomes included Antral follicle count (AFC), modified Kupperman scale, basal FSH level, LH level, FSH/LH ratio, positive pregnancy, clinical pregnancy, early spontaneous abortion, ongoing pregnancy, and ectopic pregnancy. Discussion: This study provides clinical evidence and theoretical support for the treatment of DOR with conception vessel acupuncture and moxibustion, so as to guide and improve the efficacy of acupuncture and moxibustion. Trial registration: Acupuncture-Moxibustion Clinical Trial Registry ChiCTR2400080471. Registered on 30 January 2024.